Die Chimäre einer Globalen Öffentlichkeit: Internationale Medienberichterstattung und die Legitimationskrise der Vereinten Nationen - Ulrich, Dirk-Claas (transcript, 2016)
Is there a global public sphere? This book shows how, despite the UN's rhetoric of the existence of a global public sphere, that we can no longer speak of such a thing.